GEOLOGICAL CONTRIBUTION TO THE TECTONO- STRATIGRAPHY OF THE NAFPLION AREA (NW ARGOLIS, GREECE) - Photiades, A. (Bulletin of the Geological Society of Greece, 2010)
The geological mapping in scale 1:5.000 in the greater Nafplion area indicated a Tertiary nappe stack of different Pelagonian-originated tectonic units structurally overlying the Subpelagonian series of Argolis Peninsula. The Subpelagonian series as lower unit is characterized by a shallow-water carbonate platform of Middle Triassic to Early Jurassic age, locally deep-water ammonitico-rosso facies and red cherts and is overlain by a tectono-sedimentary ophiolitic melange of Malm age. After the compressive tectonic phase of late Jurassic, the Nafplion area at that time records a severe extensional intra-Cretaceous syn-rift phase leading to the deposition of diachronous Meso-autochthonous Cretaceous limestone deposits rich in faulted-derived limestone breccias series, topped by deep-water limestone of Campanian-Maastrichtian and then from Lower Tertiary pelagic limestone facies passes upwards into post-Ypresian flysch. The different Pelagonian telescoped tectonic units were contemporaneously overthrusting northwestward, over the Subpelagonian post-Ypresian flysch sequence, during the Late Eocene compressive phase, are successively characterized by: (a) a middle tectonic unit of a flyschoidal melange of Late Cretaceous-Early Tertiary age, like the Adheres Melange surfaces in Southern Argolis, associated with various carbonate and ophiolite tectonosomes trapped and carried within this highly disrupted terrigenous flyschoidal melange and, (b) an upper unit consists of Cretaceous carbonate slivers bearing serpentinite sole (Palamidi, Akronafplia, Profitis Ilias, Aria) and/or of Middle Triassic-Early Jurassic carbonate platform slices. The above nappe stacking may be connected with the Eocene continental collision of the Hellenides.